2023
DOI: 10.1177/00084174221145820
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the Research Activities of Canadian Occupational Therapy and Occupational Science Faculty Members

Abstract: Background. There is a lack of knowledge on the scope and nature of the research by faculty members in occupational science (OS) and/or occupational therapy (OT) programs in Canada. Purpose. To describe the research activities of faculty members in these programs and directions. Method. A cross-sectional survey was distributed to 173 faculty members across all 14 Canadian OT that addressed: 1) research topics and methods, 2) populations, and 3) funding. Findings. Based on respondents ( N  =  121), research is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
(43 reference statements)
2
2
0
Order By: Relevance
“…Most of the studies in this review were mapped to the evidence‐based practice (80%) and participation in everyday life priority areas (71%). This was consistent with findings from Jarus et al (2023) who did not use the WFOT research priorities but identified participation (63.6%) as the most commonly reported research area for Canadian occupational therapy researchers. However, alignment with some of the other research priorities was low.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Most of the studies in this review were mapped to the evidence‐based practice (80%) and participation in everyday life priority areas (71%). This was consistent with findings from Jarus et al (2023) who did not use the WFOT research priorities but identified participation (63.6%) as the most commonly reported research area for Canadian occupational therapy researchers. However, alignment with some of the other research priorities was low.…”
Section: Discussionsupporting
confidence: 90%
“…Smith (2017) suggests that occupational therapy should be looking forward to the next 100 years in terms of technology development as more will become available to support participation for people with disability. Yet only 14% of publications in this review were mapped to technology, consistent with the 12.6% of articles identified by Jarus et al (2023). Working with communities has also been identified as an area for occupational therapy practice where communities can be assisted to improve their health and wellbeing (Lauckner et al, 2019) but only 10% of publications in this review were mapped to community development.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations